Tragical serpents: their symbology in Euripides’ Medea and Bacchae (Iter, 2022)
Animality represents a basic referent of a polyvalent language, adaptable tothe most varied discursive contexts of positive or negative sign. Animalization ofcharacters and animal references in tragedy present a wealth of analysis that invites tofocus on these issues in Euripides’s plays. This is especially remarkable in Medea andBacchae. The playwright deploys an extreme use of this resource rich in mechanisms as well as in degrees of dramatic intensity. As an animal with the most ambiguoussymbolic values, serpents have established a particular relationship with the sacredand with the origins, apart from being one of the most important chthonic creatures.The linking of Dionysus and Medea with the animal world is overwhelming. Bothcharacters in the mythological tradition involve representations that bring themcloser to wilderness and monstrosity. It is from this perspective that we propose toanalyze the ophidian references to detect a series of mechanisms that operate in bothworks. We find a set of remissions in intimate connection with the great victimizers(Medea and Dionysus) based on certain symbolic animals and monsters that arerelated to these tragic characters.
Keywords: animalization, serpent, Medea, Dionysus